Congestion management in overlay networks. (18th March 2020) - Benamrane, Fouad; Sanhaji, Ali; Niger, Philippe; Cadro, Philippe
Network congestion is a problem that could affect seriously the network performance if it is not taken into consideration especially in overlays network used in cloud environments. While congestion in these environments happens in the underlay network, the source of the congestion may come from virtual machines located in the overlay. Our contribution is to provide real-time mechanisms to manage congestion from overlay networks. The steps of congestion reaction are as follows. First, we monitor and identify a congestion event using explicit congestion notification (ECN) mechanism. Second, we take a decision to react to congestion when the estimated congestion during monitoring exceeds a tolerated threshold. Last, we react to the congestion to improve network performance by limiting the throughput of virtual machines in the overlay network. Through a proof of concept, we show the efficiency of our implementation to react to the congestion when the threshold exceeded the defined limits.